Can improved cassava genotypes from the breeding program substitute the adopted variety for gari production? Biophysical and textural attributes approach - Awoyale, W.; Oyedele, H.A.; Adesokan, Michael; Alamu, Emmanuel Oladeji; Maziya-Dixon, Busie (Frontiers Media, 2022)
The use of the biophysical and textural attributes of gari/eba to determine the possible substitution of an adopted cassava variety (TMBE419) with the improved genotypes from the breeding program was evaluated in this study. Standard methods were used for the characterization of the biophysical and textural attributes of the gari/eba from di􀀀erent cassava roots. It was observed that the mean of the biophysical attributes of the gari is swelling power (SWP) 12.46%, dispersibility 59.70%, water absorption capacity (WAC) 474.60%, peak 355.82 RVU, breakdown 111.02 RVU, and final 423.07 RVU viscosities, peak time 4.91min, pasting temperature 80.14◦C,moisture content 3.92%, ash content 0.98%, starch content 71.98%, amylose content 31.47% and cyanogenic potential (CNP) content 0.47mg HCN/kg. There were significant differences (p < 0.05) in all the biophysical attributes of the gari samples. The instrumental texture attribute of the eba is hardness 40.46 N/m2, mouldability 0.93, and stretchability 1.04. The sensory texture attributes depict that all the eba was moderately soft, sticky, and mouldable. Significant differences (p < 0.05) exist in the instrumental and sensory texture attributes of the eba samples. The PCA shows that gari made from TMS14F1285P0006 and TMS13F1053P0010 genotypes may have similar behavior in terms of dispersibility, SWP, and peak and breakdown viscosities to that of the TMBE419 variety. Also, the stickiness of the eba prepared from the TMS14F1285P0006 and TMS13F1053P0010 genotypes may be the same as that of the TMBE419 variety. Therefore, TMS14F1285P0006 and TMS13F1053P0010 genotypes may be good replacements for producing gari/eba in place of the TMBE419 variety.